CD27- IgD- B cell memory subset associates with inflammation and frailty in elderly individuals but only in males - Nevalainen, Tapio (Immun Ageing, 2019)
BACKGROUND: Immunosenescence, i.e. the aging-associated decline of the capacity of the immune system, is characterized by several distinct changes in the number and functions of the immune cells. In the case of B cells, the total number of CD19+ B cells is lower in the blood of elderly individuals than in the younger ones. CD19+ B cell population contains several subsets, which are commonly characterized by the presence of CD27 and IgD molecules, i.e. naïve B cells (CD27- IgD+), IgM memory (CD27+ IgD+), switched memory (CD27+ IgD-) and late memory (CD27- IgD-). This late memory, double negative, population represents cells which are nondividing, but are still able to produce inflammatory mediators and in this way maybe contributing to the aging-associated inflammation, inflammaging. Here we have focused on the role of these B cell subsets in elderly individuals, nonagenarians, in the regulation of inflammation and inflammation-associated decline of bodily functions. As the biological aging process demonstrates gender-specific characteristics, the analyses were performed separately in males and female. RESULTS: A subcohort of The Vitality 90+ study (67 nonagenarians, 22/45 males/females and 40 young controls, 13/27 males/females) was used. Flow cytometric analysis indicated that the total percentage of the CD19+ cells was ca. 50% lower in the nonagenarians than in the controls in both genders. The proportions of these four B cell subsets within the CD19+ populations were very similar in young and old individuals. Thus, it seems that the aging-associated decline of the total CD19+ cells affects similarly all these B cell subsets. To analyze the role of these subsets in the regulation of inflammation, the correlation with IL-6 levels was calculated. A significant correlation was observed only with the percentage of CD27- IgD- cells and only in males. As inflammation is associated with aging-associated functional performance and frailty, the correlations with the Barthel index and frailty score was analyzed. Again, only the CD27- IgD- population demonstrated a strong male-specific correlation. CONCLUSIONS: These data show that the CD27- IgD- B cell subset demonstrates a strong pro-inflammatory effect in nonagenarians, which significantly associates with the decline of the bodily functions. However, this phenomenon is only observed in males.